Tenmile ebook - Dallas, Sandra (Sleeping Bear Press, 2022)
Life in 1880 Tenmile, Colorado, isn't easy. But it's all that 12-year-old Sissy Carlson knows. She's lived here her whole life, watching her father, the local doctor, tend to the town's citizens. And while the mountain setting is gorgeous, Tenmile is a rough gold mining town. It often feels like there's just a thin line between life and death. Mining is a hard job; men are hurt or even killed. Sissy sees the same thin line between the haves and the have-nots as she assists her father in his practice, seeing firsthand the personal and not-always-private struggles of his patients. Now that she's older, Sissy is starting to think of the world beyond Tenmile and where she might fit in. What opportunities might she find if she could just get away? What kind of future does Tenmile offer, especially for a girl? A poignant coming-of-age middle grade novel by New York Times-bestselling author Sandra Dallas.